Analysis of Risk Factors for Hypoparathyroidism After Total Thyroidectomy - Ru, Zhou; Mingliang, Wang; Maofei, Wang; Qiaofeng, Chen; Jianming, Yuan (Frontiers in Surgery, 2021)
Objective To analyze the risk factors of hypoparathyroidism after total thyroidectomy. Methods Clinical data of patients who undergo total thyroidectomy in the Luwan Branch of Ruijin Hospital Affiliated to Medical College of Shanghai Jiaotong University was collected from January 2015 to December 2018, retrospectively. Logistic regression was used to analyze the risk factors associated with transient and long-term hypoparathyroidism. Results A total of 537 patients were collected. The patients' average age included in the study was 47.3±12.7 years old, including 135 males (25.1%) and 702 females (74.9%). There were 194 patients (36.1%) with transient postoperative hypoparathyroidism, and 21 patients (3.9%) had long-term postoperative hypoparathyroidism. After multivariate analysis, the main risk factors related to postoperative transient hypoparathyroidism were gender (P=0.038, OR 0.686), combined lymph node dissection (P=0.008, OR 1.569), and the maximum diameter of the thyroid (P= 0.011, OR 1.192), second operation (P=0.001, OR 1.974), preoperative blood calcium (P<0.001, OR 0.028). The main risk factors associated with long-term postoperative hypoparathyroidism are combined with lymph node dissection (P=0.011, OR 1.594), maximum thyroid diameter (P=0.032, OR 1.254), and PTH on the first day after surgery (P<0.001, OR 1.199). Conclusions Gender, combined lymph node dissection, maximum thyroid diameter, a second surgery, and preoperative blood calcium are risk factors for transient hypoparathyroidism after thyroid surgery. The combined lymphatic dissection and the thyroid gland's maximum diameter are risk factors for long-term hypoparathyroidism after thyroid surgery. PTH on the first day after surgery has a predictive effect on patients with long-term hypoparathyroidism.